2012
DOI: 10.1038/labinvest.2011.169
|View full text |Cite
|
Sign up to set email alerts
|

A pyrosequencing assay for the quantitative methylation analysis of the PCDHB gene cluster, the major factor in neuroblastoma methylator phenotype

Abstract: Epigenetic alterations are hallmarks of cancer and powerful biomarkers, whose clinical utilization is made difficult by the absence of standardization and of common methods of data interpretation. The coordinate methylation of many loci in cancer is defined as 'CpG island methylator phenotype' (CIMP) and identifies clinically distinct groups of patients. In neuroblastoma (NB), CIMP is defined by a methylation signature, which includes different loci, but its predictive power on outcome is entirely recapitulate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
33
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 31 publications
5
33
0
Order By: Relevance
“…Recent genome-wide studies are starting to reveal a role for DNA methylation outside such genomic contexts [12,41,[47][48]. However, the great majority of studies that have investigated DNA methylation in neuroblastoma were focused significantly on the analysis of CpG islands and promoter regions of genes with potential prognostic relevance [20][21][22][23][24][25][26][27][28][29]. Such studies have rarely provided insights into DNA methylation changes outside these well-described sites.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Recent genome-wide studies are starting to reveal a role for DNA methylation outside such genomic contexts [12,41,[47][48]. However, the great majority of studies that have investigated DNA methylation in neuroblastoma were focused significantly on the analysis of CpG islands and promoter regions of genes with potential prognostic relevance [20][21][22][23][24][25][26][27][28][29]. Such studies have rarely provided insights into DNA methylation changes outside these well-described sites.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, low-risk neuroblastoma showed mean methylation levels similar to normal adult tissues, specifically to adult cerebellum. Previous studies have shown that the simultaneous methylation of multiple CGIs, the CpG island methylator phenotype (CIMP), is associated with poor prognosis in neuroblastoma [21][22][23]. However, in neuroblastoma the CIMP is exemplified by the methylation state of the PCDHB gene family (32)(33)(34).…”
Section: Epigenetic and Transcriptional Fingerprint Of Neuroblastomamentioning
confidence: 99%
See 2 more Smart Citations
“…The PCRs were performed using IMMOLASE TM DNA Polymerase (Bioline, Aurogene) according to the manufacturer's instructions. The resulting amplicons were subjected to pyrosequencing analysis to confirm the appropriateness of the result considering the influence of the annealing temperature on the possible preferential amplification of the methylated compared with unmethylated template [20] and considering the presence of degenerated bases in the pyrosequencing primers [21]. The sequence of all primers, the PCR amplification conditions, and the sequence of the pyrosequenced fragments are indicated in Supplementary Table S5.…”
Section: Pyrosequencing Assaymentioning
confidence: 99%